Efficacy of some Herbal Medicines in Osteoarthritis with a Focus on Topical Agents: A Systematic Review - Ansaripour, Sadra; Dehghan, Morteza (Current Pharmaceutical Design, 2020)
Osteoarthritis (OA) is a leading cause of musculoskeletal disorders that mainly affects the elderly population. Some herbal medicines have the potential to alleviate the pain associated with OA and improve physical activity mostly through anti-inflammatory and anti-oxidative properties. The aim of this study was to investigate the effects of herbal medicines, especially topical types, on osteoarthritis. In this systematic review, the keywords “osteoarthritis”, “herbal compounds”, “herbal medicine”, “topical drug”, “hydrogels”, “cream” and “treatment” were used to search publications published from 2010 to 2019 and indexed in databases including PubMed, SCOPUS, Web of Science and Google Scholar. After screening of titles and abstracts and detection of duplicate publications, 38 eligible articles were included in the main review. We also included herbal formulations in vivo. Bioactive fractions of herbal medicines mostly worked on OA through suppression of interleukin-1β (IL-1β), inducing nuclear factor-ΚB (NF-ΚB) activation by inhibition of inhibitor of NF-ΚB (IΚBα) phosphorylation, IΚBα degradation, p65 phosphorylation, and p65 nuclear translocation, downregulation of NF-ΚB targets including COX-2 and MMPs, upregulation of collagen type II, cartilage-specific proteoglycans (CSPGs), β1-integrin, and expression of cartilage-specific transcription factor SOX-9 protein. Noticeably, herbal medicines do not produce desirable effects, thereby using their combinations with other therapeutic agents seem to exert substantial clinical outcomes. Herbal gels have demonstrated robustly significant healing effects on knee pain, stiffness and mobility. It is worth considering that because OA is a chronic disease, longer duration of the studies/trials would even lead to obtaining more reliable judgments regarding topical treatment tolerability, safety and efficacy and clarify local or systemic adverse effects. Stability and standardization of a defined amount or concentrations of herbal gels would give promising effects on OA treatment and pain relief.
Keywords: Herbal medicine